Implementation of psychiatric/psychotherapeutic support within a longitudinal health monitoring in competitive para athletes - Dallmann, P.; Leonhart, R.; Hirschmüller, A. (British Journal of Sports Medicine, 2021)
Background Longitudinal monitoring of mental health symptoms in para athletes israre, so are strategies to prevent and detect mental illnesses in this group. Ideas to lower barriers for seeking for mental help are needed.